Avaliação da duração e impacto do primeiro esquema anti-retroviral altamente potente em pacientes portadores da Síndrome da Imunodeficiência Adquirida (SIDA) em acompanhamento no Setor de Imunodeficiências doServiço de Doenças Infecciosas e Parasitárias/ Hospital das Clínicas (DIP/HC) do Centro de Treinamento e Referência em Doenças Infecciosas e Parasitárias Orestes Diniz (CTR-DIP/UFMG-PBH) em Belo Horizonte,Minas Gerais. - Flavia Andrade Ribeiro (2007)
The highly active antiretroviral therapy (HAART) improves substantially the prognosis of HIV infected patients. Finding a better regimen for the first antiretroviral treatment is one of the strategies used to improve time and quality of life of people living with HIV/AIDS. A total of 891 HIV infected patients assisted at the CTR-DIP Orestes Diniz and treated with firstantiretroviral therapy with at least three drugs initiated between 1996 and 2007, were evaluated through a longitudinal historical cohort. The patients were followed for 24 months or until interruption, abandon, changing of the regimen or death. The patients were predominantly males, white, young, single and with a low level of education. The PI regimens represented 61.5% of the prescriptions. A progressive decrease in the regimens composed with PI in the first antiretroviraltreatment was observed, in agreement with the modifications recommended by the country committee. At the end of 6 months 69% of the patients were still being treated with the first regimen, 54% at 12 months, 48% at 18 months and 39% at 24 months. The combination of AZT- 3TC-EFV was the regimen most prescribed and lesser failure. The regimens composed with NNRTI showed high efficacy and durability compared to the regimens with PI. The high frequency of regimens, well known for their less tolerability and efficacy, might be responsiblefor the worse results of the regimens composed with PI. The CD4 lymphocyte count < 200cells/ mm3, the irregular dispensation of medication and working as housekeeper were risks factors forfailure or interruption of the treatment in the multivariate analyses. The small number of patients with viral load before the beginning of the HAART impaired the correlation with the treatment duration. The intolerance/adverse effects were mainly responsible for failure of the regimen, followed by the abandon/non-adherence and by the virologic failure. When comparing drugs classes, the results showed a significant difference between the causes of interruption of the first HAART with the major percentage of intolerance/adverse effects of patients treated with PIregimens and therapeutic immunologic failure with patients treated with NNRTI. The regimens composed with EFV showed high durability and efficacy compared to the regimens contained NVP. The patients which antiretroviral regimen were interrupted or failed in the first 24 months,showed 3.9 times more chance to die until 2006. Although the advent of more potent and tolerable drugs, the lack of adherence to the drugs and the high level of adverse effects are still the most important barriers to the prolonged success of the treatment. This study brings relevant information about the durability and efficacy of HAART. However, new studies are encouraged, in special to evaluate ritonavir-boosted PI.